The Metatarsal Cortical Index as an Indicator of Insufficiency Fracture of the Foot - Christopher G. Lenz; Constance Raith; Lukas Urbanschitz; Timo O. Tondelli; Karim Eid; Richard Niehaus; Sandro Hodel (Foot & Ankle Orthopaedics, 2022)
Category: Basic Sciences/Biologics; Midfoot/Forefoot Introduction/Purpose: The diagnosis of metatarsal stress fractures is challenging. Standard imaging often shows false negative results. The aim of this study was to create reliable radiologic outcome parameters to predict insufficiency fractures of the metatarsals Methods: We performed an age- and sex-matched case-control study of patients with (n = 18) and without insufficiency fracture (n = 18) of the foot. To measure the ratio between the outer cortical border and the endosteal diameter, the MCI was developed as a novel radiographic measurement on dorsoplantar images. The MT was divided into thirds, and the width from the outer cortical border to the endosteal diameter was measured at the junction of the proximal to the middle third (proximal), at the midshaft (middle), and at the junction of the middle to the distal third (distal). The metatarsal cortical index (MCI) for each metatarsal was developed to predict an insufficiency fracture. The MTs were sequentially numbered as MT I-V. To correct for potential bias due to MT length, the Coughlin index and Maestro method were used in all patients. Results: The MCI of each metatarsal was significantly decreased in the insufficiency fracture group compared with the control group (p <.01). The MCI of the fourth ray yielded the highest area under the curve among the analyzed MCI values (area under the curve, 0.79; 95% confidence interval, 0.61-0.90). A cut-off value of 1.62 for the MCI of the fourth ray yielded a sensitivity of 78% and a specificity of 78% to predict insufficiency fracture of the foot (odds ratio, 12.25; 95% confidence interval, 2.54-58.97), and enabled accurate allocation to the insufficiency fracture group versus the control group in 74% of cases. Conclusion: A decreased MCI is associated with metatarsal insufficiency fractures and enables an accurate diagnosis in three out of four cases. Despite the highly variable anatomy and morphology of the MTs, we were able to show that the MCI is a reliable tool to determine insufficiency fracture of the MT on plain radiography. The MCI might aid clinicians in identifying insufficiency fracture, and raise the suspicion of the diagnosis without additional imaging studies.